Distal Metatarsal Articular Angle in Hallux Valgus Deformity. Fact or Fiction? A 3-Dimensional Weightbearing CT Assessment. (April 2022) - Lalevée, Matthieu; Barbachan Mansur, Nacime Salomao; Lee, Hee Young; Maly, Connor J.; Iehl, Caleb J.; Nery, Caio; Lintz, François; de Cesar Netto, Cesar
Background: The Distal Metatarsal Articular Angle (DMAA) was previously described as an increase in valgus deformity of the distal articular surface of the first metatarsal (M1) in hallux valgus (HV). Several studies have reported poor reliability of this measurement. Some authors have even called into question its existence and consider it to be the consequence of M1 pronation resulting in projection of the round-shaped lateral edge of M1 head. Our study aimed to compare the DMAA in HV and control populations, before and after computer correction of M1 pronation and plantarflexion with a dedicated weightbearing CT (WBCT) software. We hypothesized that after computerized correction, DMAA will not be increased in HV compared to controls. Methods: We performed a retrospective case-control study including 36 HV and 20 control feet. In both groups, DMAA was measured as initially described on conventional radiographs (XR-DMAA) and WBCT by measuring the angle between the distal articular surface and the longitudinal axis of M1. Then, the DMAA was measured after computerized correction of M1 plantarflexion and coronal plane rotation using the α angle (3d-DMAA). Results: The XR-DMAA and the 3d-DMAA showed higher significant mean values in HV group compared to controls (respectively 25.9 ± 7.3 vs 7.6 ± 4.2 degrees, P < .001, and 11.9 ± 4.9 vs 3.3 ± 2.9 degrees, P < .001). Comparing a small subset of precorrected juvenile HV (n=8) and nonjuvenile HV (n=28) demonstrated no significant difference in the measure DMAA values. On the other hand, the α angle was significantly higher in the juvenile HV group (21.6 ± 9.9 and 11.4 ± 3.7 degrees; P = .0046). Conclusion: Although the valgus deformity of M1 distal articular surface in HV is overestimated on conventional radiographs, comparing to controls showed that an 8.6 degrees increase remained after confounding factors' correction. Clinical Relevance: After pronation computerized correction, an increase in valgus of M1 distal articular surface was still present in HV compared to controls. Level of Evidence: Level III, retrospective case-control study.